KEHIDUPAN SOSIAL EKONOMI KELUARGA PETANI PADI SAWAH DI DESA MOLOMPAR ATAS KECAMATAN TOMBATU TIMUR KABUPATEN MINAHASA TENGGARA - Liwan, Yosua Yoel; Andaria, Kalvin Salindeho; Poli, Ellen Eva; Gystin Djein Sumilat (Fakultas Ilmu Sosial dan Hukum, 2025)
This study aims to determine the family burden, level of education, and condition of land ownership as social characteristics of lowland rice farmers in Molompar Village. The research method is descriptive-quantitative. The data collection techniques used are observation, interviews, and questionnaires. The data analysis technique uses a simple statistical mode. The results showed that lowland rice farmers have a family burden of more than two dependents, so that by working as a lowland rice farmer alone, they cannot meet the basic needs of the family. The education of lowland rice farmers is the last level of education (junior high school or equivalent), and there are still many children of rice farmers who have to drop out of school due to economic factors. The ownership of paddy fields belongs to other people, so farmers are part of cultivating farmers.